Search for associated production of Y and vector boson in pp̄ Collisions at √s = 1.8 TeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2003)
Associated production of υ and vector boson in pp̄ collisions at √s = 1.8 TeV were investigated. The CDF detector was used in the analysis. The analysis showed that υ(1S) mesons in association with W± or Z0 bosons were not observed by the CDF detector.